IMPLEMENTASI PENINGKATAN AKHLAK PESERTA DIDIK DAN STRATEGINYA - Abd. Latif (Fakultas Tarbiyah, Universitas Ibrahimy, 2021)
Character education applied to students is the essence of the learning process. Islamic religious education is one of the compulsory subjects which contains a lot of character material. So that the implementation of student morals in schools require to be considered properly. This research aims to (1) describe the forms of moral improvement of students at SMP Negeri 7 Bondowoso, (2) describe the steps for improving the morals of students at SMP Negeri 7 Bondowoso. This research using qualitative research methodology and data collection technique by observation, interview, documentation. The data was analyzed by data reduction, display, as well as taking the result and verification technique. The result of this research is the form of students' morals which consists of morals to others and morals to God. Meanwhile, the steps to improve students' morals consist of direct and indirect improvements.